Numerical Simulation of the Solidification Process of Aluminum Alloys Using ABAQUS Finite Element Software - Duc, Do Minh; Quang, Pham (European Journal of Applied Sciences, 2025)
This study presents a detailed numerical simulation of the solidification process of aluminum alloys using ABAQUS finite element software. A 2D axisymmetric thermal model was developed to capture transient temperature fields, phase transitions (solid, semi-solid, and liquid), and solidification-front propagation in a stepped mold geometry. Results show how variations in mold thickness affect thermal gradients and consequently influence microstructure and mechanical properties. The simulation highlights the critical role of cooling rates in different mold zones and offers predictive insights into potential casting defects such as porosity and shrinkage. The methodology offers a cost-effective and robust approach for optimizing mold design and thermal control in aluminum casting.